SOURCES OF LITHUANIAN ECONOMIC GROWTH: AN EMPIRICAL ANALYSIS WITH SECTORAL DATA - Žemgulienė, Jolanta (Ekonomika, 2012)
Abstract. In this paper, sources of economic growth are analyzed by an empirical investigation based on annual Lithuanian data of sectoral national accounts for the period from 1996 to 2010. The extent to which productivity variations in private Lithuanian economy can be explained by the production factors of physical as well as human capital, and inter-industry productivity spillovers and scale economies, is estimated by a regression analysis, based on the production function approach. The results have revealed that the endogenous growth model, which includes physical and human capital input variables and also variables of inter-sectoral productivity spillovers and scale economies, associated with the sectoral level of human capital, explains a considerable part of productivity growth. The factor of scale economies, related to sectoral capital investment, was not supported by the empirical investigation.Key words: economic growth, inter-industry spillovers, scale economies associated with human capital